Salem possessed : the social origins of witchcraft - Boyer, Paul S.; Nissenbaum, Stephen; Harvard University. Press (Cambridge, Massachusetts and London, England : Harvard University Press, 1974)
"The stark immediacy of what happened in 1692 has obscured the complex web of human passion which had been growing for more than a generation before building toward the climactic witch trials. Salem Possessed explores the lives of the men and women who helped spin that web and who in the end found themselves entangled in it."--Back cover.
Prologue: What happened in 1692 -- 1692 : some new perspectives -- In quest of community, 1639-1687 -- Afflicted village, 1688-1697 -- Salem Town and Salem Village : the dynamics of factional conflict -- Two families : the Porters and the Putnams -- Joseph and his brothers : a story of the Putnam family -- Samuel Parris : a pilgrim in Bethlehem -- Witchcraft and social identity -- Epilogue: To the eighteenth century.
Includes bibliographical references and index.
Keywords: Porter family; Putnam family; Witchcraft -- Massachusetts -- Salem; Witchcraft -- Social aspects -- Massachusetts -- Salem; Witchcraft -- history; HISTORY -- Social History; Porter family; Putnam family; Putnam; Porter; Witchcraft -- Social aspects; Witchcraft; Massachusetts -- Salem; Witchcraft -- Massachusetts; United States, Massachusetts, Essex, Salem -- History -- Colonial period, ca. 1600-1775.; United States, Massachusetts, Essex, Salem -- Genealogy; Hekserij; Hexenglaube; Salem, Mass; Sorcellerie -- Salem (Mass.); Putnam family; Porter family; Witchcraft -- History; Salem (Mass.) -- History; Geschichte 1600-1700.; Student Collection; Biographies; Biographies